Spremljanje strjevanja železovih litin z dilatometrijo - Mrvar, Primož (Kovine zlitine tehnologije, 1999)
The cast iron solidification and the dilatation analysis have been investigated. Computer-added dilatometer has been designed and verified into the practice. The results of measurements the dilatations in dependence of temperature and time are shown in dilataometric curves. The investigations have been taking place on the lamellate graphite and spheroidal graphite cast irons. The results have been verified by the thermal analysis and metallographic examinations. It is possible to detect exactly the precipitation of graphite as independent phase by eutectic solidification and eutectoid transformation. Therefore the information about the graphite growth in the eutectoid transformation has been enabled in order to find out the proportion between the perlite and ferrite phase in the matrix of the SG cast iron. Such investigation of melts would made possible the correction of the composition cast melt before the casting.
Keywords: dilatometrija; strjevanje; lito železo; mikrostruktura